Lafayette! ebook A revolutionary war tale. - Hale, Nathan (Nathan Hale's Hazardous Tales, 2018)
New York Times Bestselling Series! STARRED REVIEW *âAction-packed. . . . A must-buy.â â School Library Journal âThese books are, quite simply, brilliant. . . . Thrilling, bloody, action-packed stories from American history.â â New York Times Â  Meet French nobleman and American Revolutionary War hero the Marquis de Lafayette in this installment of the New York Times bestselling graphic novel series! Â  Gilbert du Motier became the Marquis de Lafayette at a young age, but he was not satisfied with the comforts of French nobility. He wanted adventure! A major general by nineteen, he was eager to prove himself in battle. When he heard about the revolution going on in America, he went overseas. Â  He fought with George Washington and Alexander Hamilton in Americaâs war for independence. Passionate about the American causeâand endearingâLafayette was accepted into the Continental Army when other French officers were not, because of his willingness to learn (and because his wealth meant that he didnât require a salary). General Washington took him under his wing, and Lafayetteâs loyalty to the commander-in-chief even saved Washington from a plot to remove him from command. Â  Lafayette would become a legend on both sides of the Atlantic and a symbol of the enduring friendship between America and France. Â  Nathan Haleâs Hazardous Tales! Read them allâif you dare! One Dead Spy: A Revolutionary War Tale (Nathan Haleâs Hazardous Tales #1) Big Bad Ironclad!: A Civil War Tale (Nathan Haleâs Hazardous Tales #2) Donner Dinner Party: A Pioneer Tale (Nathan Haleâs Hazardous Tales Book #3) Treaties, Trenches, Mud, and Blood: A World War I Tale (Nathan Haleâs Hazardous Tales #4) The Underground Abductor: An Abolitionist Tale about Harriet Tubman (Nathan Haleâs Hazardous Tales #5) Alamo All-Stars: A Texas Tale (Nathan Haleâs Hazardous Tales #6) Raid of No Return: A World War II Tale of the Doolittle Raid (Nathan Haleâs Hazardous Tales #7): Lafayette!: A Revolutionary War Tale (Nathan Haleâs Hazardous Tales #8) Major Impossible: A Grand Canyon Tale (Nathan Haleâs Hazardous Tales #9) Blades of Freedom: A Tale of Haiti, Napoleon, and the Louisiana Purchase (Nathan Haleâs Hazardous Tales #10) Cold War Correspondent: A Korean War Tale (Nathan Haleâs Hazardous Tales #11)